1987
DOI: 10.3146/i0095-3679-14-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Late Leafspot Resistance and Agronomic Traits in Peanut1

Abstract: Twenty peanut (hachis hypogaea L.) populations in F, generation from an M x N mating design involving five late leafspot (Cercosporidium personaturn)-resistant female parents and four adapted male parents were evaluated for late leafspot resistance with a detached leaf culture technique. Agronomic traits were evaluated in the field. Objectives were 1) to identlfy the best parent for agronomic traits and the best source of resistance to late leafspot, 2) determine the correlations among components of resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 7 publications
(5 reference statements)
3
21
0
1
Order By: Relevance
“…Furthermore, additive genetic variance seems to contribute predominantly to the resistance (Kornegay et al 1980; Hamid et al 1981; Anderson et al 1986; Jogloy et al 1987). Groundnut breeders across the world have developed superior varieties resistant to LLS and/or rust.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, additive genetic variance seems to contribute predominantly to the resistance (Kornegay et al 1980; Hamid et al 1981; Anderson et al 1986; Jogloy et al 1987). Groundnut breeders across the world have developed superior varieties resistant to LLS and/or rust.…”
Section: Introductionmentioning
confidence: 99%
“…Iroume and Knauft (1987) also observed that selection among crosses would be more advantageous as compared to individual plant selection or within family selection. Whereas Jogloy et al (1987) observed that selection for resistance to LLS in F 2 generation would be ineffective due to low narrow sense heritability; the contrasting observation was made by Anderson et al (1986b) who concluded from their study that individual plant selection for LLS resistance would be effective during early generations. The preponderance of additive genetic effects in the present study also supports selection for LLS resistance in early generations.…”
Section: Resultsmentioning
confidence: 97%
“…From generation mean analysis of three crosses, Jogloy et al (1999) reported that additive and dominance gene actions were important in two crosses and in the third cross in addition to additive and dominance gene actions, epistasis (additive 9 additive) was also important. From their diallel study, Jogloy et al (1987) observed highly significant general combining ability for most of the components of LLS resistance. However, they reported only low to moderate (13-68 %) broad sense heritability and low narrow sense heritability (0-12.8 %) for them.…”
Section: Introductionmentioning
confidence: 99%
“…Heritability values for both diseases are reported to range from low to high depending on the resistance level of the parents used in the study, making selection in early generations ineffective in crosses resulting from parents with low heritabilities (Jogloy et al 1987). Anderson et al (1991) reported that values for broad-sense heritability for lesion number, sporulation, and defoliation rating for early leaf spot were 0.57, 0.16, and 0.56 while those for late leaf spot were 0.74, 0.54, and 0.88, respectively.…”
Section: Breedingmentioning
confidence: 99%